2023
DOI: 10.1038/s41598-023-45412-9
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell responses during SARS-CoV-2 infection and vaccination in people living with HIV-1

Aljawharah Alrubayyi,
Emma Touizer,
Dan Hameiri-Bowen
et al.

Abstract: Natural killer (NK) cell subsets with adaptive properties are emerging as regulators of vaccine-induced T and B cell responses and are specialized towards antibody-dependent functions contributing to SARS-CoV-2 control. Although HIV-1 infection is known to affect the NK cell pool, the additional impact of SARS-CoV-2 infection and/or vaccination on NK cell responses in people living with HIV (PLWH) has remained unexplored. Our data show that SARS-CoV-2 infection skews NK cells towards a more differentiated/adap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…It has been suggested that CD4/CD8 ratio may be useful to monitor HIV-1 infection and to improve clinical decision making. Although there is not clear increase in the rate of COVID-19 among PWH in comparison with the general population, low levels of CD4+ T cells have been related to severe forms of the disease ( 44 ), and low or inverted CD4/CD8 ratio reflects a decreased capacity to respond to SARS-CoV-2 ( 45 ). Accordingly, PWH with normal CD4/CD8 ratio should be able to respond efficiently to vaccination against COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that CD4/CD8 ratio may be useful to monitor HIV-1 infection and to improve clinical decision making. Although there is not clear increase in the rate of COVID-19 among PWH in comparison with the general population, low levels of CD4+ T cells have been related to severe forms of the disease ( 44 ), and low or inverted CD4/CD8 ratio reflects a decreased capacity to respond to SARS-CoV-2 ( 45 ). Accordingly, PWH with normal CD4/CD8 ratio should be able to respond efficiently to vaccination against COVID-19.…”
Section: Discussionmentioning
confidence: 99%